A quantitative experiment on the fountain effect in superfluid helium - Amigó, M.L. (2017)
Fil: Amigó, M.L. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina